CIRBP Enhances the Function of Yak Cumulus Cells by Activating AMPK/mTOR-Mediated Mitophagy - Rui Zhang; Yan Cui; Yangyang Pan; Meng Wang; Sijiu Yu; Ruihua Xu; Wenbin Ma; Junqian Wang; Donglan Zhong; Zhengxing Jiao (Biomolecules, 2025)
Cold-inducible RNA-binding protein (CIRBP) has been reported to be involved in various cellular functions by regulating programmed cell death (PCD). However, the specific mechanism and function of CIRBP in regulating mitochondrial autophagy are still unclear. In this study, we found that CIRBP induced mitophagy through the AMPK/mTOR pathway to improve the function of yak cumulus cells (YCCs). We observed that low temperatures (32 °C) activated autophagy, increased E2 and P4 secretion, and up-regulated CIRBP expression. CIRBP overexpression activated mitophagy in YCCs, promoted cumulus diffusion, enhanced E2 and P4 synthesis and secretion, and inhibited apoptosis. CIRBP overexpression significantly attenuated the dysfunction of YCCs induced by the inhibition of mitophagy, whereas the activation of mitophagy exerted the same effect as CIRBP overexpression. DOX HCL is an AMPK/mTOR pathway inhibitor. CIRBP overexpression can successfully alleviate the inhibition of mitophagy caused by DOX HCL inhibiting the AMPK/mTOR pathway and can significantly enhance the mitophagy induced by AMPK/mTOR pathway activation in YCCs. Furthermore, we found that the increased expression of CIRBP protein alleviated the apoptosis caused by AKT pathway activation. In summary, CIRBP promoted mitophagy by activating AMPK/mTOR pathway, thereby promoting the synthesis and secretion of steroid hormones and cumulus diffusion in YCCs and enhancing YCCs survival through activating autophagy and AKT signaling pathway, and then improve the function of YCCs. Our research provided new perspectives on CIRBP’s regulation of cell death and highlighted its potential role in female reproductive systems.